Understanding cookie consent: habits and perceptions across information technology backgrounds and levels of security awareness - Kariuki, Emilia (2024)
This thesis investigates the user consent habits and perceptions of website cookies across differing information technology backgrounds and levels of security awareness. The importance for the thesis derives from the increased focus on online security, with the increasing amount of internet usage by all demographics. Website cookies are commonly defined as small files that websites use to track user activity and preferences. They can save data such as usernames, passwords and user preferences. Specific cookies are also used to identify specific users, thus making it possible to offer the user personalized advertisements and enhanced user experience. Due to international laws such as the EU’s General Data Protection Regulation (GDPR), websites are required to ask the user for permission for the use of optional cookies. This allows for research to inspect user consent habits as well as perceptions of the interaction. The research consists of two main sections, literature review and an empirical section. In the literature review section prior research is used to form a basis for the empirical section. The empirical section consists of a quantitative case study which collects information about the user’s consent habits and perception to website cookies across differing IT backgrounds and levels of security using an online survey tool. Findings from this case study show a degree of consistency with the results from the literature review. The study suggests that security awareness significantly correlates with cookie consent habits, a higher level of security awareness correlating with declining cookies more often. Interestingly, the same significant correlation was not found between IT expertise and cookie consent habits. The literature review revealed that IT expertise does not necessarily correlate with higher levels of security actions, making the results logical in that context. Additionally, the research identified significant differences in perceptions. The trend indicates that security awareness and IT expertise positively correlate with both positive and negative perceptions of website cookies.